A straightforward method to evaluate the directivity function of ultrasound imaging systems. (April 2021) - Prado, Tatiana de A.; Moura, Hector L.; Passarin, Thiago A.R.; Guarneri, Giovanni A.; Pires, Gustavo P.; Pipa, Daniel R.
Abstract: One of the main advantages of ultrasonic arrays over conventional single-element transducers is the possibility to electronically steer and focus the ultrasonic beam. Accurate beam manipulation depends on knowledge of the directivity function of the transducer elements. Usually, the directivity function is obtained through a complicated test based on measurements of the acoustic pressure field by a hydrophone over a plane or volume surrounding the transducer. In this paper, we propose a simpler method to determine the directivity function of linear arrays. Echo signals are acquired in a setup consisting of only a small reflector and a phased array transducer in an underwater assembly. Then, A-scan signals are processed to obtain the parameters that yield the experimental directivity function. We present results showing that images reconstructed with the Corrected Total Focusing Method (which accounts for both spatial amplitude dependency and directivity) can be improved if the experimental directivity function is used rather than the theoretical curve. Specifically, artifacts are reduced and the amplitudes of identical reflectors in different positions are more uniform throughout the reconstructed image.